KARTU SKOR PUJI ROCHYATI (KSPR) DALAM UPAYA SKRINING KEHAMILAN IBU RESIKO TINGGI - Eny Susanti; Zakkiyatus Zainiyah (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2020)
Danger signs in pregnancy are signs that indicate the mother or baby is in danger. If there are signs of danger, usually the mother needs to get immediate help in the hospital (hospital emergency). Based on the facts globally 830 died due to pregnancy and childbirth, and 99% occurred in developing countries including Indonesia, the measurement of the MDGs achievement decreased by 44%, 530 maternal deaths in 1990 and 303 in 2015. Based on a survey through interviews with pregnant women in Ponkesdes Kelbung, Sepuluh, Bangkalan Village is not familiar with screening for pregnancy danger signs and the tendency of the community to check with health workers if a serious problem arises. The method used to carry out community service is by collecting data on the number of pregnant women in the Ponkesdes Kelbung Village, Sepuluh, Bangkalan. Participants in the activity were 24 pregnant women in Ponkesdes Desa Kelbung, Sepuluh, Bangkalan who participated in the training and examination of IMT, ROT, and MAP. During the activity, pregnant women were very enthusiastic about the material presented. It was found that 37.5% of pregnant women in Kelbung Sepuluh Village had high-risk pregnancies and 8.3% with very high risks.